Abstract 12300: Impact of Catheter Contact Angle on Local Impedance Drop and Lesion Size Using the INTELLANAV STABLEPOINT Ablation Catheter: Insight From a Porcine Experimental Study - Matsuura, Gen; Fukaya, Hidehira; Ogawa, Emiyu; Kawakami, Sota; Yutaro, Mitani; Murayama, Yusuke; Saito, Daiki; Sato, Tetsuro; Nakamura, Hironori; Ishizue, Naruya; Oikawa, Jun; Kishihara, Jun; et al. (Circulation, 2021)
BackgroundLocal impedance (LI) at a distal tip of the ablation catheter can indirectly measure tissue temperature during radiofrequency catheter ablation (RFCA). LI decreases by RFCA, and a degree of LI drop is correlated with lesion size. However, data on the effects of catheter contact angle on LI parameters were scarce. This study aimed to evaluate the influence of catheter contact angle on LI change and lesion size in a porcine experimental model. MethodsLesions were created on porcine myocardial left ventricles by the LI and Contact force(CF)-sensing ablation catheter (INTELLANAV STABLEPOINT™). Radiofrequency ablation was performed with a power of 30 watts and a duration of 30 seconds. CF (0, 5, 10, 20, and 30g) and catheter contact angle (30°, 45°, and 90°) were changed in each set (total 120 lesions, n=8 each). LI rise by catheter contact, LI drop by RF application, and lesion size (lesion width, surface width, and lesion depth) were evaluated. ResultsThe values of LI rise increased as CF increased. Regarding the difference of catheter angles, LI rise with 90° was lower than those with 30°. The LI drop also increased as CF increased in all contact angles. The LI drop with 90° was lower than those with 30° in CF 5, 10, 20, and 30 g, respectively. Maximum lesion width and surface width were smaller in 90° than those in 30°, whereas there were no differences in maximum lesion depth except for CF 5g. The approximate curves were well fitted with a quadratic equation in all angles on LI drop vs. maximum lesion width, and lesion depth. ConclusionUnder the same CF, the values of LI drop and lesion width in 90° were significantly lower than those in 30° despite lesion depths were not different among the three angles. LI drop correlates with lesion width and lesion depth at any angle, which may be a good predictor of lesion size.